Scaffold-diverse synthesis via Petasis–sequence reactions and the discovery of IRE1α modulators - Avathan Veettil, Amrutha Krishnan (Technische Universität Dortmund, 2025)
Small molecules have long been central to pharmaceutical research, serving as therapeutic agents and effective tools for investigating biological functions. While structure-based and high-throughput screening approaches aid in drug discovery, the key challenge remains the limited exploration of chemical space, as most available small molecule libraries are dominated by flat, sp2-rich compounds. The growing number of potential therapeutic targets, driven by advances in genomics and proteomics, underscores the urgent need for novel chemistry strategies to generate diverse, structurally complex small molecules. The initial part of this thesis presents the synthesis of a diverse array of small molecules featuring polycyclic scaffolds with a high degree of sp3-hybridized carbon atoms and multiple stereogenic centers. This was achieved through three-component Petasis reaction (3C-PR) followed by intramolecular Diels–Alder reactions, as well as a sequential 3C-PR, ruthenium-catalyzed ring-closing metathesis (RCM), and intermolecular Diels–Alder reaction. Our synthetic efforts led to the formation of a collection of epoxyisoindoles and pyridazino[4,3-c]azepines in good yields, within 2-3 steps. The stereochemistry of the products was confirmed via single-crystal X-ray diffraction analysis. Our findings highlight the broad substrate scope and versatility of Petasis–sequence reactions in accessing previously unexplored polycyclic scaffolds with favorable predicted drug-like properties and potential biological relevance. The subsequent chapter focuses on the dual kinase and endoribonuclease (RNase) enzyme IRE1α, a key regulator of the unfolded protein response (UPR) and RNA metabolism. Dysregulation of the IRE1α–XBP1 axis of UPR has been implicated in the pathogenesis of multiple diseases, making IRE1α an attractive therapeutic target. A screening of a structurally diverse in-house compound library is conducted to identify new small molecule modulators of IRE1α RNase. This led to the discovery of two distinct classes of modulators: indole-based allosteric inhibitors that bind to the ATP binding pocket to suppress RNase activity, and aminopyrimidine-based activators that enhance RNase function while inhibiting its kinase activity. These compounds were further structurally modified and optimized to generate analogues with improved potency. Notably, inhibitor 54 exhibited IC50 values of 16 nM (IRE1α) and 9 nM (p-IRE1α) while activator 91 demonstrated EC50 values of 480 nM (IRE1α) and 180 nM (p-IRE1α). Comprehensive biophysical assays, mechanistic studies, and cellular evaluations support the therapeutic potential of these small molecules as modulators of IRE1α activity. Together, this work demonstrates the capability of Petasis–sequence reactions as efficient and complexity-generating strategies in constructing polycyclic bioactive small molecules and presents new molecular tools for exploring RNA-targeted therapeutic strategies, particularly through the modulation of IRE1α RNase activity.
Keywords: Scaffold-diversity; Petasis-sequence reactions; Polycyclic scaffolds; Ribonuclease; IRE1α; ER Stress-associated diseases; Small molecule modulators; 540; Ribonucleasen; Carbocyclen